Impact of heat stress on the performance of dairy cows: A mini-review - Ahlam Abd El Halim El Shewy (Veterinary Research Notes, 2025)
The current article was aimed at highlighting heat stress aspects in dairy cattle. Information was obtained from different online databases, mainly ScienceDirect publications. This study showed that the problem of heat stress becomes more implicated due to global warming. Dairy farms represent 20% of the livestock contribution to the global greenhouse gas emission. The temperature humidity index (THI) has been used as a monitor of the heat stress level depending on the air temperature and humidity. Dairy cows with 79 ≤ THI ≤ 83 undergo a dangerous degree of stress. In heat-stressed cows, total feed intake is decreased by 27%; subsequently, energy utilized for milk production is decreased by about 40%, and the conception rate is decreased by 35%. Also, under heat stress, not only does panting (hyperventilation) sharply increase the loss of carbon dioxide, resulting in respiratory alkalosis, but also a high sweating rate results in electrolyte imbalance due to the loss of significant quantities of potassium. Several strategies have been suggested to alleviate these adverse effects, such as (a) shading plus the evaporative cooling systems should be applied, particularly in dry climates; (b) cows must be fed diets with high energy density to decrease heat production; and (c) selecting cows that are more heat tolerant and low emitters of methane emissions. This review recommends that the suggested strategies must collaborate to improve the performance of dairy cows under heat stress, and more research is needed. [Vet. Res. Notes 2025; 5(6.000): 48-54]